Microstructural study of bearing material failure due to rolling contact fatigue in wind turbine gearbox - Maharjan, Niroj (2020)
Wind turbines in wind farm have to face harsh environmental conditions and unpredictable loading. Such unforeseen circumstances coupled with large number of turbines in a wind farm pose a great challenge for regular maintenance of turbine systems. This often leads to premature failure of the system hampering the expected energy generation. The bearings in wind turbine gearboxes are usually the first to fail prematurely. Thus, study of material alterations in bearings is becoming very significant to understand the mechanisms of failure. This paper discusses how the contact fatigue cracks appear in the bearings and the typical microstructural changes that occur due to contact force during operation. It examines the microstructural changes that occur in inner ring of 6309 deep groove ball bearings and 7209 angular contact ball bearings by using optical microscopy and scanning electron microscopy. The bearing material undergoes characteristic contact fatigue failure as the result of high loading during the long period service. With continued operation at high load, the subsurface region of inner ring of bearing experiences characteristic dark etching region and white etching bands. Even in properly lubricated system, these structural changes lead to initiation of cracks from inclusions or other sites in the subsurface region. These micro-cracks would eventually propagate towards the surface resulting in fatigue spalling. This paper reviews several theories behind such microstructural alterations and briefly investigates on possible methods to identify these changes nondestructively to provide predictive maintenance information to maximize the bearing lifetime. A timely identification of material change in bearing can be a significant step in preventing the catastrophic failure and reducing the downtime of the wind turbine due to gearbox bearing during operation.